Parrots of the wild : a natural history of the world's most captivating birds - Toft, Catherine Ann, 1950-2011; Wright, Timothy F., 1967- (University of California Press, 2015)
"A synthetic account of the diversity and ecology of wild parrots, distilling knowledge from the author's own research and from her review of more than 2,400 published scientific studies. The text covers parrots' evolutionary history, foraging, mating, and social behavior, innate intelligence, and conservation status. The book is enhanced by an array of illustrations, including photos of parrots taken exclusively in their natural habitat"--Provided by publisher.